Analisis Implementasi Akuntabilitas dan Transparansi Pengelolaan Dana Zakat di LAZ Sidogiri Cabang Bangkalan - Rahmat (Alkasb: Journal of Islamic Economics, 2022)
The focus of the study in this research is as follows: How is the Accountability of Zakat Fund Management at LAZ Sidogiri Bangkalan Branch, How is the Transparency of Zakat Fund Management at LAZ Sidogiri Bangkalan Branch, For this reason, the purpose of this study is: To find out and describe the Accountability and Transparency of Zakat Fund Management at LAZ Sidogiri Bangkalan Branch. The location of this research was carried out at LAZ Sidogiri Bangkalan Branch which is located at Jl. Pesalakan, Kec. Bangkalan, Kab. Bangkalan. The results of the analysis conducted by the authors show that most of the principles of transparency have been implemented properly. LAZ Sidogiri has implemented the principle of transparency with indicators that there is information that is easily understood and easily accessible by the public, especially muzakki, there are publications and media regarding the process of activities and financial details that can be accessed by the public, namely through financial budget reports, and reports on the distribution of zakat funds which are published through media that is directly distributed to the muzakki. In addition, the Amil Zakat Agency has also implemented the principle of accountability as measured by the conformity between implementation and standard implementation procedures, reports that are made simply, namely only zakat receipt reports and financial budget reports for one period. And with the increase in muzakki, this is one of the proofs that the public's trust in the administrators of zakat has increased.